Representations of Poverty and Place Using Geographical Text Analysis to Understand Discourse - Paterson, Laura L.; Gregory, Ian N. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores a novel methodological approach which combines analytical techniques from linguistics and geography to bring fresh insights to the study of poverty. Using Geographical Text Analysis, it maps the discursive construction of poverty in the UK and compares the results to what administrative data reveal. The analysis draws together qualitative and quantitative techniques from corpus linguistics, critical discourse analysis, Geographical Information Science, and the spatial humanities. By identifying the place-names that occur within close proximity to search terms associated with to poverty it shows how different newspapers use place to foreground different aspects of poverty (including employment, housing, money, and benefits), and how the London-centric nature of newspaper reporting dominates the discursive construction of UK poverty. This book demonstrates how interdisciplinary research methods can illuminate complex social issues and will appeal to researchers in a number of disciplines from sociology, geography and the spatial humanities, economics, linguistics, health, and public policy, in addition to policymakers and practitioners.